Unusual Site‐Selective Doping in Layered Cathode Strengthens Electrostatic Cohesion of Alkali‐Metal Layer for Practicable Sodium‐Ion Full Cell. Issue 6 (22nd December 2021) - Peng, Bo; Chen, Yanxu; Wang, Feng; Sun, Zhihao; Zhao, Liping; Zhang, Xiaolei; Wang, Wentao; Zhang, Genqiang
Abstract: P2‐type Na0.67 Ni0.33 Mn0.67 O2 is a dominant cathode material for sodium‐ion batteries due to its high theoretical capacity and energy density. However, charging P2‐type Na0.67 Ni0.33 Mn0.67 O2 to voltages higher than 4.2 V (vs. Na + /Na) can induce detrimental structural transformation and severe capacity fading. Herein, stable cycling and moisture resistancy of Na0.67 Ni0.33 Mn0.67 O2 at 4.35 V (vs. Na + /Na) are achieved through dual‐site doping with Cu ion at transition metal site (2a) and unusual Zn ion at Na site (2d) for the first time. The Cu ion doping in 2a site stabilizes the metal layer, while more importantly, the unusual alkali‐metal site doping by Zn ion serves as O 2‐ Zn 2+ O 2‐ "pillar" for enhancing electrostatic cohesion between two adjacent transition metal layers, preventing the crack of active material along the a – b ‐plane and restraining the generation of O2 phase upon deep desodiation. This unique dual‐site‐doped [Na0.67 Zn0.05 ]Ni0.18 Cu0.1 Mn0.67 O2 cathode exhibits a prominent cyclability with 80.6% capacity retention over 2000 cycles at an ultrahigh rate of 10C, demonstrating its great potential for practical applications. Impressively, the full cell devices with [Na0.67 Zn0.05 ]Ni0.18 Cu0.1 Mn0.67 O2 and commercial hard carbon as cathode and anode, respectively, can deliver a high energy density of 217.9 Wh kg ‐1 and excellent cycle life over 1000 cycles. Abstract : Unusual site‐selective doping with Cu ion at transition metal site (2a) and unusual Zn ion at Na site (2d) for P2‐ Na0.67 Ni0.33 Mn0.67 O2 can effectively restrain P2–O2 phase transition and prevent material crack due to the enhanced electrostatic cohesions between two transition metal layers, leading to ultralong life span sodium‐ion full cell.